The Relation of Pregnant Women's Class Participation and Childbirth Preparation in Third-Trimester Pregnant Women - Meliyanti, Selvi; Hidayah, Nurul; Dona, Sismeri; Maolinda, Winda (Lambung Mangkurat University, 2024)
The maternal mortality rate remains high both globally and in Indonesia. Approximately 75% of these deaths are due to complications during pregnancy and childbirth. Therefore, childbirth preparation is essential. Active participation in pregnant women's class activities at least four times during pregnancy is recommended. However, class participation at the Long Kali Community Health Center is still low, with only 53% attendance. This research aims to determine the relationship between active participation in pregnant women's classes and preparation for childbirth among third-trimester pregnant women in the Long Kali Community Health Center's working area. The research method used is descriptive analytics with a cross-sectional approach. The research population consisted of all third-trimester pregnant women who participated in pregnant women's class activities, with a sample size of 33. A questionnaire was used as the instrument for data collection. Data were analyzed using the Chi-square test. The results showed that the majority of respondents were aged 20-35 years (72.7%), had low education levels (48.5%), were not employed (81.8%), had multiparous parity (51.5%), actively participated in class activities (63.6%), and were prepared for childbirth (57.6%). The statistical test results showed a p-value of 0.001, indicating a significant relationship between active participation in pregnant women's classes and childbirth preparation among third-trimester pregnant women in the Long Kali Community Health Center's working area.